'Green tech' geographies: the role of technology in contemporary frontier-making processes - Lehmann, Rosa; Wiertz, Thilo (Environment and planning. C, Politics and space, 2025)
Research on resource frontiers has documented how technologies meant to support global sustainability regularly contribute to regional environmental degradation, social injustices, and political conflicts. However, while such dynamics are inextricably bound to changes in socio-technical systems, many studies consider technology as a boundary condition, rather than an integral part of frontier making. To better understand the processes of de/territorialization that shape contemporary green tech frontiers, we suggest integrating theoretical propositions about frontier making with insights from science and technology studies (STS). Our contribution is thus twofold. First, we review recent scholarship on frontiers and carve out conceptual underpinnings. Second, we propose integrations with conceptual ideas from STS, particularly following critical, feminist and post-colonial voices. In particular, we suggest that frontier research has much to gain from considering the spatiality of frontiers as relational, imagined, and experimental. While our main contribution is conceptual, we illustrate our theoretical arguments based on a selective review of research on geographical and political repercussions of emerging green hydrogen projects and infrastructures. We conclude that a more in-depth consideration of technology in frontier research opens new perspectives on transregional dimensions of frontier making and power relationships across scales.
Gesehen am 22.01.2026